Exercise acutely increases circulating endothelial progenitor cells and monocyte-/macrophage-derived angiogenic cells - Rehman, Jalees; Li, Jingling; Parvathaneni, Lakshmi; Karlsson, Gudjon; Panchal, Vipul R.; Temm, Constance J.; Mahenthiran, Jo; March, Keith L. (Journal of the American College of Cardiology, 2004)
We investigated whether a single episode of exercise could acutely increase the numbers of endothelial progenitor cells (EPCs) and cultured/circulating angiogenic cells (CACs) in human subjects. Endothelial progenitor cells and CACs can be isolated from peripheral blood and have been shown to participate in vascular repair and angiogenesis. We hypothesized that exercise may acutely increase either circulating EPCs or CACs. Volunteer subjects (n = 22) underwent exhaustive dynamic exercise. Blood was drawn before and after exercise, and circulating EPC numbers as well as plasma levels of angiogenic growth factors were assessed. The CACs were obtained by culturing mononuclear cells and the secretion of multiple angiogenic growth factors by CACs was determined. Circulating EPCs (AC133+/VE-Cadherin+ cells) increased nearly four-fold in peripheral blood from 66 ± 27 cells/ml to 236 ± 34 cells/ml (p < 0.05). The number of isolated CACs increased 2.5-fold from 8,754 ± 2,048 cells/ml of peripheral blood to 20,759 ± 4,676 cells/ml (p < 0.005). Cultured angiogenic cells isolated before and after exercise showed similar secretion patterns of angiogenic growth factors. Our study demonstrates that exercise can acutely increase EPCs and CACs. Given the ability of these cell populations to promote angiogenesis and vascular regeneration, the exercise-induced cell mobilization may serve as a physiologic repair or compensation mechanism.